Seeking Structure in Collections: Desire for Control Motivates Engagement in Collecting - Cao, C Clark; Brucks, Merrie; Reimann, Martin (Journal of Consumer Research, 2025)
Abstract Across six studies, we provide converging and robust lab and field evidence that the fundamental human desire for control motivates consumer engagement in collecting, defined as the act of acquiring items that belong to an existing collection. This is because consumers who desire control seek structure, which is created when interconnected components form a holistic entity. A collection can provide such a structure, as it comprises related items that together create a whole set. Hence, as consumers add items to a collection, they are also manifesting a structure. Indeed, we demonstrate that desire for control’s motivating effect on engagement diminishes when structure-seeking is hindered or when the collection is far from completion. This work contributes to extant consumer research by identifying desire for control as a fundamental motivation of collecting behavior, explaining when and why consumers work toward completing their collections, and explicating the structured nature of collecting. Of practical relevance, we provide implications for the enhancement of consumer well-being; the design, positioning, and communication of collectible products; and the creation of policies regulating the collectibles market.